1990
DOI: 10.1021/la00096a024
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir-Blodgett manipulation of poly(3-alkylthiophenes)

Abstract: Langmuir-Blodgett (LB) multilayer thin films were fabricated from mixed monolayers containing stearic acid and various poly(3-alkylthiophenes). It has been found that mixed LB films containing as much as 80 mol % of poly(3-alkylthiophenes) form stable monolayers at the air-water interface that can be deposited onto solid substrates as Y-type films by the vertical lifting method. The LB films exhibit well-defined layered structures as determined by optical, capacitance, and X-ray diffraction measurements. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 0 publications
4
40
0
Order By: Relevance
“…2. In all the three cases, the absorption spectra in the as-deposited state show a broad peak at 500 nm, characteristic of POT, confirming the presence of the polymer in the composite multilayers [22]. In the case of POTCdA multilayer exposed to H 2 S gas ( Fig.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…2. In all the three cases, the absorption spectra in the as-deposited state show a broad peak at 500 nm, characteristic of POT, confirming the presence of the polymer in the composite multilayers [22]. In the case of POTCdA multilayer exposed to H 2 S gas ( Fig.…”
Section: Resultssupporting
confidence: 54%
“…There has recently been considerable interest toward their application in electroluminescent and photovoltaic devices [20,21]. In the present work, the composite monolayer methodology [22,23], in which a non amphiphilic polymer is mixed with a suitable metal ion containing amphiphilic molecule, has been used to develop composite LB multilayers of poly(3-octylthiophene) (POT) with cadmium arachidate (POT-CdA), zinc arachidate (POT-ZnA) and copper arachidate (POTCuA).The composite multilayers were subjected to post deposition H 2 S exposure to grow CdS, ZnS and Cu 2 S nanoclusters within the polythiophene -arachidic acid (POT-AA) composite multilayers. The formation of semiconducting nanoclusters in the POT-AA matrix was studied by FTIR and UV-VIS spectroscopies and X-ray reflectivity was used to study the layered structure of the multilayers.…”
Section: Introductionmentioning
confidence: 98%
“…It exhibits high electrical conductivity in its oxidized state with chemical stability under ambient conditions. As a promising conducting polymer with environmental stability and sensitivity, PEDOT is commonly used in sensors for detecting ammonia, nitrogen dioxide and other toxic organicvapours (Watanabe et al 1990;Hu and Xu 2000). It is reported that during the synthesis of PEDOT, the solubility of 3,4-ethylenedioxythiophene (EDOT) is facilitated by the use of a water-dispersible polymer electrolyte, viz.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has recently been extended to develop CdS nanocluster containing polyaniline LB films using precursor polyanilinecadmium arachidate (PANI-CdA) composite LB multilayer [14]. The composite monolayer methodology in which a non-amphiphilic polymer is mixed with suitable metal ion containing amphiphilic molecule provides a simple approach to develop these polymer based precursors [15]. The composite precursors can subsequently be subjected to post deposition treatments to generate semiconducting nanoclusters within the layered polymer matrix.…”
Section: Introductionmentioning
confidence: 99%